Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Klein, Shannon G.; Pitt, Kylie A.; Lucas, Cathy H.; Hung, Shiou-Han; Schmidt-Roach, Sebastian; Aranda, Manuel; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Responses of cnidarian-Symbiodiniaceae associations to warming are determined, in part, by high-frequency temperature variability. Yet, the role of such variability in determining specific maximum temperature thresholds of cnidarian holobionts (the ecological units comprised of cnidarian hosts and associated microorganisms, including Symbiodiniaceae) remains untested. Here we contrasted the thermal resilience (that is the ability to resist stress) of a model symbiotic cnidarian from the Red Sea (jellyfish of the genus Cassiopea) under stable and diel oscillating temperature conditions that provide night-time reprieves from daily maximum temperatures. Holobionts were subjected to two thermal trajectories; one that increased but plateaued at 2 °C below identified bleaching thresholds and another that increased incrementally until holobionts bleached. We used behavior, growth, photochemical efficiency, Symbiodiniaceae (symbiont) cell density, and total chlorophyll cell content to characterize thermal resilience and examined Symbiodiniaceae community composition responses at 1 and 13 days of exposure, and post-bleaching. Lower night-time temperatures, resulting in lower daily mean temperatures, allowed holobionts to withstand daily maximum temperatures close to their bleaching thresholds for two extra days than those under stable maximum temperature conditions. Lower night-time temperatures increased the bleaching threshold of the holobionts, whereby holobionts exposed to night-time thermal reprieves tolerated a more extreme daily mean temperature of 40.6 ºC and reached a daily thermal maxima 4 ºC higher than those under stable temperature conditions. However, post-bleaching observations indicate that night-time temperature reprieves did not prevent symbiont cell or pigment loss. Symbiodiniaceae communities were unaffected by lower night-time temperatures and no directional changes indicative of symbiont shuffling/ selection of thermally tolerant lineages were observed. We show that stable experimental treatments may fail to accurately identify maximum thermal thresholds of non-calcifying cnidarians and limit their relevance to in situ environments that are often characterized by high levels of temperature fluctuations.